Pengaruh Variasi Produk, Harga Dan Cita Rasa Terhadap Loyalitas Konsumen Pada Tahu Sadis Joyoboyo Kota Kediri - Ria Setya Agustin (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This research aims to determine the influence of product variation (X1), price (X2) and taste (X3) variables on consumer loyalty (Y) in Tahu Sadis Joyoboyo, Kediri City. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the saturated sampling method, the number of samples in the research was 85 respondents from Tahu Sadis Joyoboyo, Kediri City. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test.The results of the research obtained the multiple linear regression equation Y= -4.748 + 0.470X1 + 0.283X2 + 0.569X3 and the results of the t test for product variation, price and taste variables had a partially significant effect on consumer loyalty with sig < 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that product variety, price and taste have a simultaneous and significant effect on consumer loyalty to Tahu Sadis Joyoboyo Kediri.